2010
DOI: 10.1111/j.1365-2672.2009.04634.x
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide analysis of biofilm‐forming Candida albicans

Abstract: Aim:  The major objective of the study was to analyse exopolysaccharide produced by a biofilm forming‐clinical strain of Candida albicans. Methods and Results:  The biofilm‐forming ability of C. albicans recovered from infected intrauterine devices (IUDs) was evaluated using XTT (2,3‐bis[2‐methoxy‐4‐nitro‐5‐sulfophenyl]‐2H‐tetrazolium‐5‐carboxanilide) reduction assay. The morphological characteristics of the biofilm were assessed using scanning electron microscopy (SEM), atomic force microscopy (AFM) and confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 33 publications
1
53
0
1
Order By: Relevance
“…Our data clearly showed a dose-dependent decrease in biofilm thickness, which could be explained by the differences in cell morphology observed by light microscopy, as well as differences in the amounts of EPS in samples treated with SRM-S-8 compared to controls. C. albicans biofilms secrete a thick layer of EPS, which is associated with immobilization and inhibition of antifungal drug penetration into the biofilm (46,47). A notable reduction in EPS production in biofilms exposed to SRM-S-8 can be related to the reduced biomass and modified morphology of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly showed a dose-dependent decrease in biofilm thickness, which could be explained by the differences in cell morphology observed by light microscopy, as well as differences in the amounts of EPS in samples treated with SRM-S-8 compared to controls. C. albicans biofilms secrete a thick layer of EPS, which is associated with immobilization and inhibition of antifungal drug penetration into the biofilm (46,47). A notable reduction in EPS production in biofilms exposed to SRM-S-8 can be related to the reduced biomass and modified morphology of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolabelling studies have further revealed the presence of galactomannan, galactosaminogalactan and a-1,3 glucans (Beauvais et al, 2007;Loussert et al, 2010). C. albicans biofilms usually contain glucose (16-32.2 %), hexosamine (3.3 %), proteins (5 %), phosphorus (0.5 %) and uronic acid (0.1 %) as well as mannose, rhamnose and galactose in the matrix (Al-Fattani & Douglas, 2006;Baillie & Douglas, 2000;Lal et al, 2010). However, C. tropicalis biofilm matrix comprises mainly hexosamine (27.4 %), with smaller amounts of other carbohydrates (3.3 %, including 0.5 % glucose), protein (3.3 %) and phosphorus (0.2 %) (Al-Fattani & Douglas, 2006).…”
Section: Characterization Of the Biofilm Matrixmentioning
confidence: 99%
“…By contrast, glucose is the major component of Candida and Aspergillus fumigatus biofilms (Al-Fattani & Douglas, 2006;Baillie & Douglas, 2000;Beauvais et al, 2007;Lal et al, 2010;Silva et al, 2009). In A. fumigatus biofilms, the EPS consists of glucose (74 %), mannitol (18 %), trehalose (3 %), glycerol (5 %), and melanin and proteins (2 %) (Beauvais et al, 2007).…”
Section: Characterization Of the Biofilm Matrixmentioning
confidence: 99%
“…The N-linked glycan portion of this glycoprotein is composed of mannose and rhamnose and is believed to be involved in the adherence of the fungus to dermal tissue (34). The opportunistic human pathogen Candida albicans, the causal agent of candidiasis, when grown under conditions that favor biofilm production secretes a large exopolysaccharide composed of rhamnose, mannose, glucose, and glucosamine (35). However, under normal growth conditions, the yeast and hyphal forms lack rhamnose.…”
Section: Discussionmentioning
confidence: 99%